Race, rhetoric, and technology : searching for higher ground - Banks, Adam J. (Adam Joel) (Mahwah, NJ : Lawrence Erlbaum ; Urbana, Ill. : National Council of Teachers of English, 2006)
"In this book Adam Banks uses the concept of the Digital Divide as a metonym for America's larger racial divide, in an attempt to figure out what meaningful access for African Americans to technologies and the larger American society can or should mean. He argues that African American rhetorical traditions - the traditions of struggle for justice and equitable participation in American society - exhibit complex and nuanced ways of understanding the difficulties inherent in the attempt to navigate through the seemingly impossible contradictions of gaining meaningful access to technological systems with the good they seem to make possible and at the same time resisting the exploitative impulses that such systems always seem to present."--BOOK JACKET.
Introduction: Looking for Unity in the Midst of Madness: Transformative Access as the ONE in African American Rhetoric and Technology Studies -- Oakland, the Word, and the Divide: How We All Missed the Moment -- Martin, Malcolm, and a Black Digital Ethos -- Taking Black Technology Use Seriously: African American Discursive Traditions in the Digital Underground -- Rewriting Racist Code: The Black Jeremiad as Countertechnology in Critical Race Theory -- Through This Hell Into Freedom: Black Architects, Slave Quilters, and an African American Rhetoric of Design -- A Digital Jeremiad in Search of Higher Ground: Transforming Technologies, Transforming a Nation.
Includes bibliographical references (p. 147-152 ) and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: African Americans -- Communication; Digital divide -- United States; Technology -- Social aspects -- United States; Rhetoric -- Social aspects -- United States; Racism -- United States; African Americans -- Social conditions -- 1975-; African Americans -- Intellectual life; United States -- Race relations; Electronic books